IN SEARCH OF CONSTITUTIONALITY: FREEDOM OF EXPRESSION AND INDONESIA’S ANTI-PORNOGRAPHY LAW - R. Herlambang Perdana Wiratraman (Universitas Airlangga, 2012)
In 2008 vehement debates about the freedom of expression divided Indonesia, after the government resubmitted a bill for Anti-Pornography to Parliament. The various sides employed all kinds of arguments and perspectives, the main ones being religious versus human rights and pluralism. The main problem of the new law is its vague and very broad definition of pornography, which could threaten women’s rights, cultural expression and press freedom. In the context of democratization in Indonesia post Soeharto, freedom of expression has been progressively promoted, particularly by the adoption of a Constitutional guarantee for freedom of expression. Nevertheless, the constitutionality of freedom of expression still needs to be comprehensively re-explored in order to advance human rights and democracy development.Key words: Anti-Pornography, Freedom of Expression, Human Rights